Increasing Students' Learning Interest through Problem-Based Learning Supported by QR Code-Based Snakes and Ladders Media - Melsyani Pali; Ayuni Banne; Asriani Asriani; Regina Putri M; Vera Amanda; Adel Rizka Nabhil; Juwita Crestiani (Journal of Excellence in English Language Education, 2026)
This study was conducted to address the low level of fifth-grade students' interest in learning science, particularly the topic of the human digestive system, at SDN 25 Sabbamparu. Preliminary questionnaire results showed that students' average learning interest was only 56%, indicating a low level of engagement. This condition was mainly caused by teacher-centered instruction, limited use of learning models, and a lack of interactive learning media. As a result, students were less active and less enthusiastic during the learning process. The purpose of this study was to improve students' learning interest through the implementation of the Problem-Based Learning (PBL) model assisted by QR Code-based Snakes and Ladders media. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 20 fifth-grade students. Data were collected through a learning interest questionnaire and observation sheets and analyzed using descriptive quantitative and qualitative techniques. The findings showed that students' learning interest improved in each cycle, as reflected in the indicators of enjoyment, interest, attention, and participation. Therefore, it can be concluded that the Problem-Based Learning model assisted by QR Code-based Snakes and Ladders media effectively increased fifth-grade students' interest in learning science at SDN 25 Sabbamparu.